2014
DOI: 10.1186/1472-6963-14-366
|View full text |Cite
|
Sign up to set email alerts
|

Patient, surgeon, and healthcare purchaser views on the use of decision and communication aids in orthopaedic surgery: a mixed methods study

Abstract: BackgroundDespite evidence that decision and communication aids are effective for enhancing the quality of preference-sensitive decisions, their adoption in the field of orthopaedic surgery has been limited. The purpose of this mixed-methods study was to evaluate the perceived value of decision and communication aids among different healthcare stakeholders.MethodsPatients with hip or knee arthritis, orthopaedic surgeons who perform hip and knee replacement procedures, and a group of large, self-insured employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The patients had an overall positive perspective of consultation recordings. Sixteen studies (7 RCTs and 9 CS) reported that most participants found recordings useful or beneficial, with a range of 55 to 98% across studies . However, listening to the recording was distressing (3‐18%) or a source of anxiety (19‐26.8%) for small proportions of participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The patients had an overall positive perspective of consultation recordings. Sixteen studies (7 RCTs and 9 CS) reported that most participants found recordings useful or beneficial, with a range of 55 to 98% across studies . However, listening to the recording was distressing (3‐18%) or a source of anxiety (19‐26.8%) for small proportions of participants.…”
Section: Resultsmentioning
confidence: 99%
“…There were reservations about the amount of time that recordings might require in an already overloaded clinical setting . However, researchers reported that recordings did not substantially increase the length of consultations, and some even found it was an efficient means of promoting the doctor‐patient partnership .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations